Distributed DC/DC converter system - Maintaining voltage stability and efficiency optimization while regulating several converters - Johansson, Markus; Tepp, Isabella (My University, 2024)
Abstract This thesis is about the investigation of a new concept regarding the supply of the low voltage side in battery electrical vehicles. The concept is about supplying the low voltage side with a multilevel converter (MLC). A control strategy was tested that is based on distributing different set voltages to each converter. The system was meant to regulate itself with no other information other than the input voltage and output voltage. The system needs to fulfil the requirements of LV124. The test sequences performed showed that a system of three converters can handle power loads ranging from approximately 20−600 W, while still fulfilling the LV124 requirement. The test sequences were performed on a system of converters with different set voltages as well as with the same set voltage. The result was that the test case with converters on the same set voltage performed better regarding both the overall efficiency as well as the voltage stability. However, the theory behind this thesis and the simulated models counter this result, meaning that a system with different set voltages would improve the overall efficiency. This unpredicted result can be concluded to be the cause of a hardware that is still in the early stages. With further development of the hardware to improve efficiency and control strategy to improve voltage stability of the system, this MLC system could possibly supply the low voltage side.
Keywords: Keywords: DC/DC converter, multilevel converter, battery electrical vehicle, set/target voltage